Coupling diode laser desorption with plasma ionization in mass spectrometry for analytical and biomedical applications - Knodel, Alexander (Technische Universität Dortmund, 2021)
This thesis focuses on the coupling of laser desorption with plasma ionization in mass spectrometry for analytical and biomedical applications. A diode laser is used to trigger thermal desorption of substances from a surface. For this reason, a metal-isolator sandwich structure is developed and conceptually tuned to analytical demands on the basis of a microscope slide, lithography and sputtering. The neutral desorbate is then ionized by a flexible, atmospheric pressure micro plasma and is finally detected by a mass spectrometer. Different analyte classes are investigated to evaluate the method, ranging from analytical standards to complex samples. These insights are extended to an automated imaging of biological tissue, which requires an adaption of the substrate design. The inherent laser-based and thermal surface effects are intensively studied and optimized to the imaging. As a result, the imaging of biological samples is simplified, faster and can be carried out in ambient air without the need of a chemical matrix, which can be applied to routine analysis in life sciences. The limits of the method are finally evaluated.

Diese Arbeit beschäftigt sich mit der Kopplung von Laser-Desorption mit Plasma-Ionisierung für die Massenspektrometrie von analytischen und biomedizinischen Proben. Bei dieser Messmethodik wird ein Diodenlaser zur thermisch gesteuerten Desorption von Proben von einer Oberfläche benutzt. Auf Basis von Objektträgern, der Lithografie und der Kathodenzerstäubung wird eine zweilagige Metall-Isolator Substratstruktur für die Laser-Desorption entwickelt und auf die analytischen Anforderungen optimiert. Das durch die Laser-Desorption entstehende neutrale Desorbat wird mittels eines flexiblen, bei Atmosphärendruck arbeitenden Mikroplasmas ionisiert und schließlich mit einem Massenspektrometer detektiert. Die Methode wird an verschiedenen Analytklassen evaluiert, die von analytischen Standards bis zu komplexen Proben reichen. Als Erweiterung der analytischen Standards wird eine automatisierte Bildgebung an biologischen Proben vorgestellt, welche eine abgewandelte Substratstruktur erfordert. Die damit einhergehenden Laser-basierten und thermischen Oberflächeneffekte werden untersucht und zur Optimierung der Methodik herangezogen. Dadurch lassen sich biologische Proben einfacher, schneller und unter Umgebungsbedingungen ohne chemische Matrix untersuchen, was in der Routineanalytik in den Lebenswissenschaften Anwendung finden kann. Schließlich werden die Grenzen der Messmethode eruiert.
Keywords: Diode laser desorption; Plasma ionization; Ambient mass spectrometry; 530; Laser